Risk factors for delayed kidney graft function from a deseased donor - A. V. Shabunin; P. A. Drozdov; I. V. Nesterenko; D. A. Makeev; O. S. Zhuravel; S. A. Astapovich (Трансплантология (Москва))
Aim. To determine statistically significant risk factors for delayed renal graft function. To assess the impact of delayed kidney graft function on the development of other complications, graft and recipient survival.Material and methods. In 237 consecutive kidney transplant recipients (from June 2018 to December 2021), we assessed its function in the early postoperative period. Delayed function was considered to be the need for hemodialysis in the first week after surgery. Among the donor factors, the type of donor, age, body mass index, the presence of vasopressor support, the time the donor was in intensive care, and the maximum level of creatinine during the follow-up were evaluated. Recipient risk factors include age, gender, body mass index, presence/absence and amount of urine, presence of preformed anti-HLA antibodies and/or repeated kidney transplantation, number of mismatches for six HLA antigens, number of mismatches for HLA-DR, presence and type of renal replacement therapy, etiology of end stage kidney disease. Among the perioperative risk factors are the duration of cold preservation, the time of second warm ischemia, the volume of intraoperative blood loss, the intraoperatively determined renal arterial resistive index of the renal graft, and the maximum concentration of tacrolimus in the first 4 days after kidney transplantation. After that the relationship between the presence of delayed kidney graft function and the development of early postoperative complications was assessed and its effect on the long-term survival of grafts and recipients was analyzed.Results. Out of 237 cases, 9 showed no function of the transplanted kidney, and therefore the grafts were removed. The incidence of delayed renal graft function was 24.5% (58/237). According to the results of a univariate analysis, a statistically significant relationship with the development of delayed kidney graft function had donor body mass index (p=0.019), male gender of the recipient (p=0.048), recipient body mass index (p=0.038), amount of urine (p=0.003), anuria (p=0.002), presence of preformed antibodies (p=0.025), repeated transplantation (p=0.002), time of second warm ischemia (p=0.036), intraoperative renal arterial resistive index (p=0.004) and maximum tacrolimus concentration in the first 4 days (p=0.022). In the multivariate model, donor body mass index >30 kg/m2 and peak tacrolimus concentration >23 ng/mL in the first 4 days were statistically significant (p=0.018 and p=0.025, respectively). A trend towards statistical significance was noted in the presence of oligoanuria before kidney transplantation (p=0.066) and resistance index >0.75 after surgery (p=0.056). One-year renal transplant survival in the absence and presence of delayed kidney graft function was 92.4% and 87.7%, two-year survival was 89.4% and 76.1%, respectively. The effect of delayed kidney graft function on graft survival was statistically significant (p=0.01), while overall recipient survival did not differ between the groups.Conclusion. During the univariate analysis, we identified 9 statistically significant factors, of which at least 3 are potentially modifiable. In the multivariate model, the most significant modifiable risk factor was an increased concentration of tacrolimus, which prompted the authors to reconsider the existing immunosuppressive protocol at the City Clinical Hospital n.a. S.P. Botkin. We consider the search for modifiable statistically significant risk factors for patients, their analysis and implementation of preventive measures to be an important task for each kidney transplant center.